Adsorption of fluoride from aqueous solution using biochar prepared from waste peanut hull. (29th January 2020) - Kumar, Pawan; Prajapati, Anuj Kumar; Dixit, Shobhit; Yadav, Vijay Laxmi
Abstract: In the present study, cost-effective biochar was prepared from waste peanut hull powder (PHP) and utilized as an adsorbent for the removal of fluoride from aqueous solution by adsorption experiment. Different techniques such as FTIR, BET, SEM, and EDX were used to analyze the surface functionality, surface area, surface morphology, and elemental composition of PHP biochar adsorbent, respectively. The batch experiments were carried out to optimize various effecting parameters like initial pH, contact time, PHP biochar adsorbent dose, initial concentration of Fluoride ion in solution, and reaction temperature. The maximum removal efficiency of PHP biochar adsorbent was 88.21% for the 10 mg l −1 fluoride concentration at pH 7 with 8 g l −1 biochar dose. For the isotherm study, adsorption equilibrium data were linearly fitted with experimental data to explain the adsorption process. Thermodynamic analysis results show that the adsorption of Fluoride onto PHP biochar adsorbent was a spontaneous, exothermic, and feasible process under experimental condition. Kinetic study of the adsorption process reveals that the pseudo-second-order model best fitted with experimental data as compared to the pseudo-first-order model.